PENGARUH PENGALAMAN AUDITOR DAN ORIENTASI ETIKA TERHADAP KEPUTUSAN ETIS AUDITOR NEGARA DENGAN KOMITMEN PROFESIONAL SEBAGAI VARIABEL INTERVENING - Hapsari, Niken Nindya (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The objective of this study to examine The influence of auditor experience and ethical orientation on making ethical decision of governmental auditor, using professional commitment as an intervening variable. This research was developed from research Butt (1988), Zeigenfuss dan Singhapakdi (1994) also Windsor and Ashkanasy (1995) by changing professional commitments as an intervening variable on making ethical decision of auditor.The research was conducted using survey methods of governmental auditor who worked on the State Audit Office of the Representative Office of East Java Province is distributed directly to the response rate of 85%. The unit of analysis were auditors with 100 respondents as samples. The analysis data technique in testing the hypothesis is path analysis.The results of this study indicated that first, the experience of auditors, ethical orientation influenced professional commitment and ethical orientation also commitment influenced ethical decision, meanwhile the auditor's experience did not influence the ethical decision. Second, these finding suggested that the professional commitment as an intervening variable of auditor experience and ethical orientation to the auditor's consideration of ethical decisions.The results concluded the auditor's experience and ethical orientation are two important issues related to professional commitment and ethical decision making. In towards the previous auditor experience and high ethical orientation could improve with good professional commitments as well as ethical decisions. Â